Progress of research on the diagnosis and treatment of bone cystic echinococcosis - Meng, Yibin; Ren, Qian; Xiao, Jun; Sun, Haohao; Huang, Yiping; Liu, Yaqing; Wang, Shan; Wang, Sibo (Frontiers in Microbiology, 2023)
Bone cystic echinococcosis (CE) is one of the most complex and dangerous of all echinococcoses. The lack of typical imaging features and clinical manifestations makes diagnosis and treatment of this disease difficult. X-ray and computed tomography (CT) images of bone CE are similar to those of bone cysts, giant-cell bone tumors, and bone metastases, but magnetic resonance imaging (MRI) shows good diagnostic value due to excellent soft-tissue imaging features. Serological tests cannot be used as a definitive diagnostic method for bone CE due to cross-reactivity, which can lead to false-positive or false-negative results. The development of novel antigens can open new frontiers in the diagnosis of the disease. Currently, views conflict on how to diagnose and treat bone CE. Both surgical and pharmacological treatments can be used, but determining which is appropriate is difficult due to the different sites and clinical manifestations of bone CE. Radical resection is not indicated for large-bone injuries, and Pharmacotherapy becomes important. This article reviews the progress of research into the pathogenesis and clinical manifestations of, and diagnostic strategies and treatment options for, bone CE. We aimed to provide a reference for clinical diagnosis and -treatment options.